GREEN ON SCREEN, VALUE IN WALLET: HOW INSTAGRAM DRIVES SUSTAINABLE CONSUMPTION BEHAVIOR - Potu, Tania Monica (Bisma: Jurnal Bisnis dan Manajemen, 2025)
Social media serves as an important marketing tool in shaping consumer perceptions of sustainable product quality. This study aims to analyze how factors in social media marketing efforts—namely entertainment, interaction, customization, and electronic Word of Mouth—affect Green Perceived Quality and its impact on Willingness to Pay Premium Price. This research focuses on @thebodyshopindo Instagram account, which actively and transparently educates consumers about sustainability and environmentally friendly products. This research model develops five main hypotheses. H1, H2, H3, H4 examined the influence of each variable of social media marketing—entertainment, interaction, customization, and electronic Word of Mouth—on Green Perceived Quality. Furthermore, H5 evaluates whether Green Perceived Quality has a significant effect on Willingness to Pay Price Premium. The research method uses a quantitative approach (survey) that targets Body Shop product customers in Surabaya and have purchased the products. The collected data were analyzed using SPSS 22. The findings of this study are expected to provide insight into the effectiveness of social media marketing, especially entertainment, interaction, and customization, moreover electronic Word of Mouth in shaping green perceived quality and encouraging willingness to pay premium price.